Dynamic response limit of high-speed railway bridge under earthquake considering running safety performance of train - Liu, Xiang; Jiang, Li-zhong; Xiang, Ping; Lai, Zhi-peng; Feng, Yu-lin; Cao, Shan-shan (Journal of Central South University, 2021)
Due to the wide railway network and different characteristics of many earthquake zones in China, considering the running safety performance of trains (RSPT) in the design of high-speed railway bridge structures is very necessary. In this study, in order to provide the seismic design and evaluation measure of the bridge structure based on the RSPT, a calculation model of RSPT on bridge under earthquake was established, and the track surface response measure when the derailment coefficient reaches the limit value was calculated by referring to 15 commonly used ground motion (GM) intensity measures. Based on the coefficient of variation of the limit value obtained from multiple GM samples, the optimal measures were selected. Finally, the limit value of bridge seismic response based on RSPT with different train speeds and structural periods was determined.